Spectrofluorimetric Study on Inclusion Behaviour of p-Sulfonated Calix[4,6]arene with 1,10-Phenanthroline - Du, Qian; Chen, Cai-Ping; Liu, Hai-Long; Du, Li-Ming; You, Jun-Chen; Chang, Ya-Fen (Asian Journal of Chemistry, 2015)
The supramolecular interaction of 1,10-phenanthroline (Phen) with p-sulfonated calix[n]arenes (SCnA, n = 4, 6) were studied using spectrofluorimetry, 1H NMR and molecular modeling calculations. The interaction mechanism of the inclusion complex was discussed and the various factors affecting the inclusion process were examined. It was found that the dramatic quenching of the fluorescence intensity of 1,10-phenanthroline was observed with the addition of the SCnA (n = 4, 6). This was due to 1,10-phenanthroline react with SCnA (n = 4, 6) to form stable complex. 1H NMR titration spectra testified that 1,10-phenanthroline was penetrated into the hydrophobic cavity of SCnA (n = 4, 6). This finding was confirmed using molecular dynamics calculations and the thermodynamic parameters of the complex. The calculated stability constant results showed that the SC6A-Phen complex was more stable than SC4A-Phen.